Lipid altering potential of moringa oleifera lam seed extract and isolated constituents in Wistar rats (2020)
The use of natural products have become popular because of their minimal adverse effect, cost effectiveness and accessibility. Moringa oleifera, is a valued plant that has found use ethnomedicinally and economically. The leaves have been investigated in various researches for different activities. This study is aimed at evaluating the seeds for its serum lipid profile altering activities in animal models. Five groups of five animals (120-150 g) per group were made obese by feeding with a high fat diet (HFD) for 10 weeks. The basal lipid profile was determined, and treatment commenced with methanol extracts of Moringa oleifera seed (MOSE) at 100 and 200 mg/kg b w for 6 weeks. Control groups were the Orlistat treated (50 mg/kg b w), untreated and normal diet groups. The antihyperlipidemic activity in-vivo and an enzyme anti lipase assay in-vitro were determined respectively. The characterisation of isolated compounds and derivative was by spectroscopic techniques. A significant decrease in Very Low Density Lipoprotein cholesterol (VLDLc) at p< 0.01 was observed across the five groups when compared with the standard Orlistat. A significant increase in High Density Lipoprotein cholesterol (HDLc) at p< 0.01 was observed in the group treated with 200 mg/kg MOSE. However, a dangerous significant increase in Athereogenic index (AI) was observed in the group treated with 100mg/kg MOSE The derived 4- acetyl benzylisothiocyanate-O –α-L rhamnopyranoside (2) from isolated 4- hydroxybenzylisothiocyanate-O-α-L rhamnopyranoside (1) revealed the highest activity of 99.17% at 0.5 mg/mL. The methanol extract of Moringa oleifera seed could alter lipid profile and a structure activity relationship was observed with respect to the isolated compound and its derivatized analogue.